Mobile health-based digital intervention to improve ARV compliance and nutritional intake in PLHIV at Bandarharjo Health Center - Rahayu Winarti; Rozaq Isnaini Nugraha; Iq Balurrochman; Nanang Bagus Setiawan; Niken Sukesi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Low adherence to antiretroviral (ARV) therapy and inadequate nutritional intake remain persistent challenges among People Living with HIV/AIDS (PLHIV) in Indonesia, contributing to suboptimal treatment outcomes and reduced quality of life. Mobile health (mHealth), which utilizes mobile devices for health interventions, offers a promising solution by facilitating personalized, accessible, and continuous patient support. This study aimed to assess the effectiveness of an Android-based mHealth application, SEHAT+, in improving ARV adherence and nutritional intake among PLHIV at the Bandarharjo Health Center, Semarang. A total of 41 active PLHIV undergoing ARV therapy were recruited from March to May 2025. Descriptive and paired t-test analyses were conducted to compare adherence and intake before and after the intervention. The mean ARV adherence score increased from 62,3 (SD = 10,5) to 84,9 (SD = 8,1), and the nutritional intake score improved from 58,7 (SD = 11,2) to 79,2 (SD = 9,6), both showing statistically significant changes (p < 0,001). SEHAT+ features included medication reminders, dietary logs, multimedia-based nutrition education, and online consultation forums. The findings indicate that mHealth interventions can significantly enhance both medication compliance and nutritional behavior in PLHIV. Community-driven digital tools such as SEHAT+ have the potential to strengthen primary healthcare responses to HIV/AIDS in resource-constrained settings.